Spinning the Web : a guide to serving information on the World Wide Web - Fisher, Yuval (New York : Springer, 1996)
The Internet has exploded in popularity, mainly due to the World Wide Web. Spinning the Web brings together WWW reference material and examples of WWW usage to help you get the most from this powerful new medium. It contains a detailed explanation of how the WWW works and shows you how to use the WWW effectively. Aimed at the intelligent reader who is comfortable with computers, the book discusses how to set up WWW sites, how to ensure site security, how to present information effectively, how to create multimedia documents, how to process forms and other user data, and how to use the latest WWW technology.
1. What, How, Where? -- 2. How the Web Works -- 3. HTTP -- 4. Servers -- 5. Security -- 6. HTML -- 7. HTML Reference -- 8. Advanced HTML Examples -- 9. CGI Scripts -- 10. Tricks -- 11. WWW Utilities -- 12. Java and JavaScript -- 13. VRML -- App. A Uniform Resource Locators -- App. B Country Code Domain Names -- App. C Strftime Format Strings.
Includes bibliographical references (p. 483-506) and index.
Keywords: World Wide Web; Web servers